Organizing Matters - Guy Mundlak (ILERA Publication series, 2020)
Organizing Matters demonstrates the interplay between two distinct logics of labour's collective action: on the one hand, workers coming together, usually at their place of work, entrusting the union to represent their interests and, on the other hand, social bargaining in which the trade union constructs labour's interests from the top down. The book investigates the tensions and potential complementarities between the two logics through the combination of a strong theoretical framework and an extensive qualitative case study of trade union organizing and recruitment in four countries - Austria, Germany, Israel and the Netherlands. These countries still utilize social-wide bargaining but find it necessary to draw and develop strategies transposed from Anglo-American countries in response to continuously declining membership.